Macau, Bali and the Malay World: A Gastronomic Perspective - Annabel Jackson; Michael John Hitchcock; Putu Diah Sastri Pitanatri (Universitas Udayana, 2024)
Macau’s location on the South China Sea suggests that any syncretic activity would have been of Sinitic-Portuguese variety. However, the situation is rather more nuanced, as the culture of the Macanese people, who consider themselves the ‘sons of the land’, reflects Portuguese colonial activity across the Indian Ocean and especially Malacca. Links between Macau and the ‘Malay World’ are deep and complex, and this paper approaches this issue through historical and political analysis, but also through the specifics of etymology and cuisine. The paper also draws comparisons with other ‘creolised’ cuisines in Southeast Asia such as Peranakan food in Malaysia and Western-Indonesian hybrids that have arisen in the tourism context of Bali. Given the importance played by women in preparing dishes for Portuguese men in Macau, parallels are drawn with the role of enslaved Hindu-Balinese women in colonial Batavia (Jakarta) who prepared pork dishes for their Dutch masters.